Protease from jute endophyte Micrococcus luteus MBL-Bac7 functions as a potential bating agent for the leather industry (Journal of Bangladesh Academy of Sciences, 2022)
Ever since the discovery of jute endophytes, testing their potential for commercial uses has been a matter of interest. Considering the same, jute endophyte Micrococcus luteus MBL-Bac7, capable of producing extracellular proteases, was selected for in vitro and in silico analysis to assess its role as a bating agent required in rawhide processing. The presence of extracellular protease was confirmed from the plate assay. As the enzyme is tested for commercial use, the effect of various metal ions and reaction conditions (pH, temperature) have been optimized. The protease activity appears to be retained even at 85°C. It also showed significant activity in a wide range of pH (pH 3.0-8.5). Metal ion Mn2+ increased the protease activity significantly, but Fe2+, Zn2+, and Co2+ ions showed the opposite effect. Molecular identification of the protease was done from the whole genome sequence data. Using PSORTb v.3.0.2, SecretomeP-1.0, TMHMM-2.0, and protein molecular weight software, the physicochemical properties of the protease were predicted. The isolated protease shared a strong evolutionary link with Micrococcus species' S8 family serine peptidase. Finally, in the bating of cowhide, effects similar to that of commercial agents were obtained during finger prick, lastometer, and tensile tests. The findings of this study corroborate the possibility of using this protease as a potential bating agent. However, further studies are necessary to reduce the production cost for higher yield and commercialization.J. Bangladesh Acad. Sci. 46(1); 31-43: June 2022